(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
The rapid advancement of AI technology presents new opportunities for developing critical thinking skills among future English teachers. This study explores how AI-based tools, such as chatbots, automated feedback systems, and adaptive learning platforms, enhance analytical reasoning, problem-solving, and decision-making.